Bivariate MIMIC Analysis of Pasture Management and Prescribed Grazing Practices Used by Beef Cattle Producers - Kristen Holley; Kimberley L. Jensen; Dayton M. Lambert; Christopher D. Clark (Journal of Agricultural and Resource Economics, 2020)
This study applies a bivariate Multiple IndicatorÐMultiple Causation model to examine farm and operator characteristics associated with the likelihood of using pasture management (PM) and prescribed grazing (PGR) practices. Data are from a survey of cattle operations. Most commonly used practices included adjusting livestock and pasture fertilization. Least used were geotextiles in trafficked areas and buffering sensitive areas. Use of PM practices was income sensitive. Land stewardship and government conservation incentive views influenced PGR. Results suggest complementarities between most PGR and PM practices. However, those with higher opportunity costs and off-farm benefits (e.g., stream crossings) are not complementary with other practices.